2019
DOI: 10.1016/j.compbiomed.2019.01.018
|View full text |Cite|
|
Sign up to set email alerts
|

Acceleration of spleen segmentation with end-to-end deep learning method and automated pipeline

Abstract: Delineation of Computed Tomography (CT) abdominal anatomical structure, specifically spleen segmentation, is useful for not only measuring tissue volume and biomarkers but also for monitoring interventions. Recently, segmentation algorithms using deep learning have been widely used to reduce time humans spend to label CT data. However, the computerized segmentation has two major difficulties: managing intermediate results (e.g., resampled scans, 2D sliced image for deep learning), and setting up the system env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A variety of deep-learning algorithms have been applied for spleen segmentation, including 2D and 3D U-Net based models, some of which combine a post-processing pipeline [ 15 , 16 , 17 , 20 , 22 , 23 , 25 , 26 , 28 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. More advanced methods include the use of transformers [ 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A variety of deep-learning algorithms have been applied for spleen segmentation, including 2D and 3D U-Net based models, some of which combine a post-processing pipeline [ 15 , 16 , 17 , 20 , 22 , 23 , 25 , 26 , 28 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. More advanced methods include the use of transformers [ 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, this method has demonstrated a relatively high level of accuracy, with a mean error of 6% in the spleen volume calculation in the testing patient cohorts, and a strong correlation of the axial measurements with the spleen volume [ 12 , 13 ]. However, in other studies, especially in cases involving individuals with splenomegaly or spleen disorders, this method has been shown to produce relatively large errors, with a low correlation between the axial measurements and the spleen volume [ 14 , 15 , 16 ], as the shape of the spleen can significantly deviate from the formula of volume–shape approximation. Alternatively, for an accurate spleen volume estimation, manual segmentation should be performed by a radiologist for the spleen for each MRI slice, which has been demonstrated to be time-consuming and labor-intensive [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we developed deep learning structures to automatically segment the PA region using MRI T1 and T2 images. Recently, there were abundant reported studies developing AI algorithms for segmentation of abdominal organs or structures including pancreas (16), liver (17,18), spleen (35,36), gallbladder (37), kidney (38,39), the local lesions of stomach (40), etc. However, there is no report of PA region segmentation using AI algorithms.…”
Section: Discussionmentioning
confidence: 99%